Strengthening Community Health Volunteer Competence through the Griya SIPAKABERU Program for Stunting Prevention - Auliyah Rofiatul Adawiyah; Anindia Sifa Hijri; Fahyul Fahyul; Ishak Bachtiar (PT. Global Research Collaboration, 2025)
The Griya SIPAKABERU (Integrated Healthy Village Program) is a community engagement initiative designed to enhance maternal and child health services by strengthening the competence of community health volunteers (posyandu cadres). The program focused on training in child growth monitoring, nutrition education, and appropriate parenting practices as preventive measures against stunting. The methods included pre-tests, participatory lectures, hands-on practice through the SIPATUA (Child Growth Monitoring Attitude) framework, and post-tests for evaluation. Results indicated a significant improvement in cadres’ knowledge: prior to the intervention, most were categorized as low to very low, while post-intervention assessments showed the majority achieving high to very high scores. In addition to knowledge gains, cadres demonstrated improved skills in providing nutrition education and monitoring child growth. Challenges included limited rural health infrastructure and low parental awareness regarding child nutrition. The Griya SIPAKABERU program has proven effective in strengthening community health volunteer capacity and supporting stunting prevention in rural communities. Sustained infrastructure support and cross-sectoral collaboration are required to ensure program continuity and scalability.